(untitled) (UNIZIK Journal of Educational Management and Policy, 2023)
This study investigated online teaching and learning as a determinant of effective education in public secondary schools in Ideato North Local Government Area of Imo State, Nigeria. The study adopted descriptive survey research design and was guided by three research questions. A random sampling technique was used to select 144 teachers drawn from the entire population of teachers (228) in Ideato North education zone of the state. A four-point scale questionnaire titled: “Online Teaching and Learning as a Determinant for Effective Education in Public Secondary Area of Imo State Questionnaire (OTLDEEPSSILGAQ:IM) was designed by the researcher, validated by experts and was used for data collection. A reliability index of 0.82 using Cronbach alpha was determined for the instrument and was adjudged to be reliable and adequate for the study. Data was analyzed using mean ratings. The findings among others revealed that, materials were not available for the teachers and students to teach and learn through online. The findings also revealed that online platforms were not always available for the students to receive the online materials that were provided for them for effective learning. It further revealed that the students were not able to learn effectively through online teaching, due to lack of materials. Based on the findings, the researcher recommended that available materials and platforms should be provided to schools for effective teaching and learning of online teaching and learning in the schools.